Bibliometric Analysis of Development of Physics Learning Media Based on Educational Games: A Systematic Literature Review: Analisis Bibliometrik Pengembangan Media Pembelajaran Fisika Berbasis Game Edukasi: Tinjauan Pustaka Sistematis - Nurfaridah (CV Aisha Edutama, 2024)
Physics is an abstract subject that requires visualization, so learning media is needed so that students are able to understand the concepts being studied. One of the learning media that displays visualization using technology is educational games. This research aims to analyze the development of educational game learning media in physics learning with a bibliometric approach using VOSViewer software. The method used in this research is bibliometric analysis. There are 6 classification clusters via VOSViewer software. The research results showed that articles were used with the titles